Sosialisasi Bahaya Stunting dan Pemberian Cookies Pisang Sebagai Solusi Pemberian Makanan Tambahan - A. Sulaeman; Laelatul ‘Azizah; Syifa Khurotun Azizah; Delia Agma Amanda; Silvian Rahmadan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The aim of this activity is to increase community understanding of the importance of proper nutritional intake to prevent stunting and malnutrition in children, as well as provide practical solutions that can be applied in everyday life. The method used in this program involves nutrition education as well as training in making banana cookies to parents and caregivers in Jabres Village. With a local wisdom-based approach, this activity not only provides knowledge, but also empowers the community to use local ingredients in stunting prevention. The results of this activity showed an increase in participants' awareness and understanding of the importance of balanced nutrition, as well as the adoption of anti-stunting banana cookies as an alternative PMT that is easy to make at home.This program is expected to be one of the effective strategies in efforts to eradicate stunting and malnutrition in the village through the use of local ingredients that are rich in nutrients.